Involving patients in HTA activities at local level: a study protocol based on the collaboration between researchers and knowledge users - Gagnon Marie-Pierre; Gagnon Johanne; St-Pierre Michèle; Gauvin François-Pierre; Piron Florence; Rhainds Marc; Coulombe Martin; Lepage-Savary Dolores; Desmartis Marie; Tantchou Dipankui Mylène; Légaré France (BMC, 2012)
Abstract Background The literature recognizes a need for greater patient involvement in health technology assessment (HTA), but few studies have been reported, especially at the local level. Following the decentralisation of HTA in Quebec, Canada, the last few years have seen the creation of HTA units in many Quebec university hospital centres. These units represent a unique opportunity for increased patient involvement in HTA at the local level. Our project will engage patients in an assessment being carried out by a local HTA team to assess alternatives to isolation and restraint for hospitalized or institutionalized adults. Our objectives are to: 1) validate a reference framework for exploring the relevance and applicability of various models of patient involvement in HTA, 2) implement strategies that involve patients (including close relatives and representatives) at different stages of the HTA process, 3) evaluate intervention processes, and 4) explore the impact of these interventions on a) the applicability and acceptability of recommendations arising from the assessment, b) patient satisfaction, and c) the sustainability of this approach in HTA. Methods For Objective 1, we will conduct individual interviews with various stakeholders affected by the use of alternatives to isolation and restraint for hospitalized or institutionalized adults. For Objective 2, we will implement three specific strategies for patient involvement in HTA: a) direct participation in the HTA process, b) consultation of patients or their close relatives through data collection, and c) patient involvement in the dissemination of HTA results. For Objectives 3 and 4, we will evaluate the intervention processes and the impact of patient involvement strategies on the recommendations arising from the HTA and the understanding of the ethical and social implications of the HTA. Discussion This project is likely to influence future HTA practices because it directly targets knowledge users' need for strategies that increase patient involvement in HTA. By documenting the processes and outcomes of these involvement strategies, the project will contribute to the knowledge base related to patient involvement in HTA.